Kolaborasi Pengabdian Masyarakat Multidisiplin: Edukasi Bahasa, Riset, dan Penyuluhan Kesehatan di SMP Negeri 23 Senopi, Papua Barat Daya - Ningsih, Sri; Uus Faizal Firdaussy; Jusni, Jusni; Enkin Asrawijaya; Erniawati, Erniawati (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2025)
Community engagement is one of the practical implementations of scientific knowledge that directly impacts society. This program is a collaboration between the National Research and Innovation Agency (BRIN) and the Midwifery Academy Tahirah Al Baeti Bulukumba, aimed at enhancing language literacy, research skills, and health awareness among students at SMP Negeri 23 Senopi,Tambray Regency, Southwest Papua. A multidisciplinary approach was applied through three main aspects: language education to improve English language proficiency and the preservation of local languages, participatory research to foster critical thinking among students, and health counseling focusing on adolescent health issues and sanitation. The methods used included interactive lectures, group discussions, practical simulations, and mentoring in basic research activities. The results of the program showed an improvement in students' understanding across these three aspects, indicated by enhanced communication skills, increased awareness of the importance of research in daily life, and behavioral changes related to healthy living practices. This collaboration demonstrates that synergy between research institutions and midwifery academia can significantly contribute to community empowerment through educational and research-based approaches.